Efficacy of a Single Dose Administration of Ibuprofen and Acetaminophen in Comparison with Acetaminophen for the Relief of Perineal Pain after Childbirth: A randomized controlled trial - Harasai, Preeyaporn; Pattanapanyasat, Noochanart (Thai Journal of Obstetrics and Gynaecology, 2020)
Objective: To determine the efficacy of a single dose of ibuprofen plus acetaminophen versus acetaminophen alone for relief from acute perineal pain after childbirth. Materials and Methods: A randomized, double-blind placebo-controlled trial was conducted on 404 women who gave birth by spontaneous vaginal delivery with mediolateral episiotomy at Queen Savang Vadhana Memorial Hospital between June 2017 and October 2017. Patients were randomized by block computer into 2 groups before delivery: one group received ibuprofen plus acetaminophen and another group received acetaminophen plus placebo. The medication was given immediately after complete perineal suturing. Perineal pain scores of both groups were assessed pre- and post-medication by visual analog scale (VAS). The adverse drug reactions were evaluated at 24 hours after medication. Results: No difference of pre-medication perineal pain score was recorded for both groups. Median of perineal pain scores were 5 vs 5 (p = 0.067), respectively. Both groups were relieved their perineal pain within 24 hours. The median different pain relief scores were 5 vs. 3 (p = 0.006), respectively. There was dramatic pain relief in the short-term in the ibuprofen plus acetaminophen group, more than for the patients in the acetaminophen alone group (at 2-hours after taken medication). There was no adverse drug reaction. Conclusion: A regimen of single dose ibuprofen plus acetaminophen has higher efficacy for relief from acute perineal pain than a conventional regimen with acetaminophen alone, and is safe to use for pregnant women after childbirth.